Selected works of Govind Ballabh Pant - Pant, Govind Ballabh; Nanda, B R (Ed) (New Delhi Oxford University Press, 2002)
The fourteenth volume covers the period from September 1951 to March 1953 and deals with the general election held under constitution and the formation of a new congress Ministry in Uttar Pradesh under the leadership of Govind Vallabh Pant who became Chie
Keywords: Pant, Govind Ballabh-Biography; Politicians-India-Biography; Pant,Govind Ballabh-Correspondence; India-Politics and government